Effects of oxygen on exercise-induced increase of pulmonary arterial pressure in idiopathic pulmonary fibrosis - Pouwels-Fry, S.; Pouwels, S.; Fournier, et al., C. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2008)
Introduction: Idiopathic pulmonary fibrosis (IPF) is a severe disease with no known effective therapy. Patients with IPF may develop severe increase of pulmonary arterial pressure (PAP) on exercise, the mechanisms of which is not clearly identified. Objectives: To determine whether oxygen may correct the increase of PAP developed during exercise in patients with IPF. Patients and methods:We performed a prospective study on patients with IPF and no hypoxaemia at rest. The absence of pulmonary hypertension (PH) at rest was confirmed by echocardiography (systolic PAP <35 mmHg). Eight patients underwent echocardiography during exercise in air and with oxygen (to maintain saturation of at least 94%). Right ventricle-right atrium gradient and cardiac output were measured at rest, after each increment and at peak.We then compared the echocardiographic results obtained for air and oxygen. Results: All patients developed significant increase of SPAP on exercise (73 ± 14 mmHg in air).Oxygen did not significantly improve SPAP on exercise (SPAP: 76 ± 15 mmHg). Echocardiographic characteristics were similar between air and oxygen except for exercise tolerance in term of workload (p=0.045) and endurance (p=0.017). Resting pulmonary function tests did not predict the occurrence of increase of PAP on exercise. Conclusion: Our results demonstrate that oxygen does not improve exercise-induced increase of PAP in patients with IPF and support the hypothesis that hypoxic vaso-constriction is not the main mechanism of acute increase of PAP during exercise.